2013
DOI: 10.1016/j.molonc.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

miR‐203 induces oxaliplatin resistance in colorectal cancer cells by negatively regulating ATM kinase

Abstract: Chemotherapy for patients with metastatic colorectal cancer (CRC) is the standard of care, but ultimately nearly all patients develop drug resistance. Understanding the mechanisms that lead to resistance to individual chemotherapeutic agents may help identify novel targets and drugs that will, in turn, improve therapy. Oxaliplatin is a common component combination therapeutic regimen for use in patients with metastatic CRC, but is also used as a component of adjuvant therapy for patients at risk for recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 51 publications
1
118
1
Order By: Relevance
“…In the present study, miR-203 was highly expressed in exosome derived from chemoresistence PCa cells. Recently, a study found that miR-203 is upregulated in three oxaliplatin (L-OHP)-resistant metastatic colorectal cancer cell (CRC) lines and induces L-OHP resistance in CRCs by negatively regulating ataxia telangiectasia mutated kinase (20). Furthermore, miR-203 promote cisplatin resistance through suppression of the suppressor of cytokine signaling 3 (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-203 was highly expressed in exosome derived from chemoresistence PCa cells. Recently, a study found that miR-203 is upregulated in three oxaliplatin (L-OHP)-resistant metastatic colorectal cancer cell (CRC) lines and induces L-OHP resistance in CRCs by negatively regulating ataxia telangiectasia mutated kinase (20). Furthermore, miR-203 promote cisplatin resistance through suppression of the suppressor of cytokine signaling 3 (21).…”
Section: Discussionmentioning
confidence: 99%
“…These factors are important in predicting the response to particular therapies. MicroRNAs act as positive biomarkers indicating sensitivity to therapy or as negative biomarkers signifying resistance to treatment and assisting in choosing the appropriate treatment regimen (Table 1) [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179] .…”
Section: Therapeutic Biomarkersmentioning
confidence: 99%
“…Pichler et al showed that miR-18a downregulation is associated with poor survival in patients with CRC and its expression could predict progression-free survival (PFS) in EGFR-targeted therapy (Pichler et al, 2014). Moreover, miR-203 was demonstrated to induce oxaliplatin, a common component MicroRNAs in Colorectal Cancer: from Diagnosis to Targeted Therapies combination therapeutic regimen for use in patients with metastatic CRC, and reverse chemoresistance by negatively regulating ATM kinase and Akt, respectively (Li et al, 2011;Zhou et al, 2014).…”
Section: Mirna As Marker For Treatment Response Predictionsmentioning
confidence: 99%